Genomic analysis of nontypeable pneumococci causing invasive pneumococcal disease in South Africa, 2003–2013. (December 2016) - Mohale, Thabo; Wolter, Nicole; Allam, Mushal; Ndlangisa, Kedibone; Crowther-Gibson, Penny; du Plessis, Mignon; von Gottberg, Anne
Abstract Background The capsular polysaccharide is the principal virulence factor ofStreptococcus pneumoniae and a target for current pneumococcal vaccines. However, some pathogenic pneumococci are serologically nontypeable [nontypeable pneumococci (NTPn)]. Due to their relative rarity, NTPn are poorly characterized, and, as such, limited data exist which describe these organisms. We aimed to describe disease and genotypically characterize NTPn causing invasive pneumococcal disease in South Africa. Results Isolates were detected through national, laboratory-based surveillance for invasive pneumococcal disease in South Africa and characterized by whole genome analysis. We predicted ancestral serotypes (serotypes from which NTPn may have originated) for Group I NTPn using multilocus sequence typing and capsular region sequence analyses. Antimicrobial resistance patterns and mutations potentially causing nontypeability were identified. From 2003–2013, 39 (0.1 %, 39/32, 824) NTPn were reported. Twenty-two (56 %) had partial capsular genes (Group I) and 17 (44 %) had complete capsular deletion of which 15 had replacement by other genes (Group II). Seventy-nine percent (31/39) of our NTPn isolates were derived from encapsulatedS. pneumoniae . Ancestral serotypes 1 (27 %, 6/22) and 8 (14 %, 3/22) were most prevalent, and 59 % (13/22) of ancestral serotypes were serotypes included in the 13-valent pneumococcal conjugate vaccine. We identified a variety of mutations within the capsular region of Group I NTPn, some of which may be responsible for the nontypeable phenotype. Nonsusceptibility to tetracycline and erythromycin was higher in NTPn than encapsulatedS. pneumoniae . Conclusions NTPn are currently a rare cause of invasive pneumococcal disease in South Africa and represent a genetically diverse collection of isolates.